'The only safe way to find a partner': rethinking sex and risk online in Abidjan, Côte d'Ivoire. Issue 1 (1st January 2020) - Thomann, Matthew; Grosso, Ashley; Wilson, Patrick A.; Chiasson, Mary Ann
ABSTRACT: Despite the Internet's global importance as a sex-seeking venue for men who have sex with men (MSM) and other sexual and gender minorities, little is known about this topic in sub-Saharan Africa. Furthermore, existing public health research offers limited insight into the sociocultural aspects of sexuality and how they articulate with patterns in online sex-seeking behavior. In 2015, we conducted survey and ethnographic research with 105 sexual and gender minorities in Abidjan, Côte d'Ivoire. Nearly half of survey respondents reported finding partners primarily online. Three quarters reported having found at least one partner online. Interviews with 24 of the survey participants revealed that a primary motivation for using online venues was that they allowed for the preservation and management of discretion and anonymity, permitting users to avoid discrimination and violence. While secondary to their strategies for managing such social risk, participants also reported using the profile features of online venues to filter out partners they perceived as presenting a risk to their sexual health. Though interview participants perceived online venues as providing a degree of protection against potential stigma and violence in offline contexts, survey data showed that over one quarter of participants had experienced extortion and/or blackmail by sexual partners they met online. By taking into account the sociocultural context of sexuality and sexual activity in Abidjan, these findings highlight the disjuncture between essentialist notions of MSM who use the Internet to find sex partners as a universal, at-risk group, and the complexity of sexual and gender minorities' experiences.